Bcl-xL Genetic Modification Enhanced the Therapeutic Efficacy of Mesenchymal Stem Cell Transplantation in the Treatment of Heart Infarction - Xiaodong Xue; Yu Liu; Jian Zhang; Tao Liu; Zhonglu Yang; Huishan Wang (Hindawi Limited, 2015)
Objectives. Low survival rate of mesenchymal stem cells (MSCs) severely limited the therapeutic efficacy of cell therapy in the treatment of myocardial infarction (MI). Bcl-xL genetic modification might enhance MSC survival after transplantation. Methods. Adult rat bone marrow MSCs were modified with human Bcl-xL gene (hBcl-xL-MSCs) or empty vector (vector-MSCs). MSC apoptosis and paracrine secretions were characterized using flow cytometry, TUNEL, and ELISA in vitro. In vivo, randomized adult rats with MI received myocardial injections of one of the three reagents: hBcl-xL-MSCs, vector-MSCs, or culture medium. Histochemistry, TUNEL, and echocardiography were carried out to evaluate cell engraftment, apoptosis, angiogenesis, scar formation, and cardiac functional recovery. Results. In vitro, cell apoptosis decreased 43%, and vascular endothelial growth factor (VEGF), insulin-like growth factor-1 (IGF-1), and plate-derived growth factor (PDGF) increased 1.5-, 0.7-, and 1.2-fold, respectively, in hBcl-xL-MSCs versus wild type and vector-MSCs. In vivo, cell apoptosis decreased 40% and 26% in hBcl-xL-MSC group versus medium and vector-MSC group, respectively. Similar results were observed in cell engraftment, angiogenesis, scar formation, and cardiac functional recovery. Conclusions. Genetic modification of MSCs with hBcl-xL gene could be an intriguing strategy to improve the therapeutic efficacy of cell therapy in the treatment of heart infarction.